Detection of Metallo-β-Lactamases and Carbapenemase Production Pseudomonas aeruginosa Isolates from Burn Wound Infection - Maharjan, Reshma; Shrestha, Basudha; Shrestha, Sanjit; Angbuhang, Khadga Bikram; Lekhak, Binod; Nepal, Krishus; Upreti, Milan Kumar (Tribhuvan University Journal of Microbiology, 2020)
Objective: The study aims to detect carbapenemase producing P. aeruginosa isolated from burn wounds and confirm MBL production by Imipenem-Combined disk method. Method: A total of 310 non-repeated clinical specimens including tissues, pus aspirates, and wound swabs were processed using standard microbiological procedure. Each identified isolate of P. aeruginosa was subjected to in vitro antibiotic susceptibility test by using modified Kirby-Bauer disc diffusion method. Two imipenem (10μg) disks were placed on the surface of the agar plate in which one of them was added with 5μl of 0.5M EDTA solution. The result was interpreted after 18 hours of incubation at 37ºC by comparing the inhibition zone of imipenem and imipenem-EDTA disks. The increase in inhibition zone by ≥7mm with imipenem-EDTA disks than imipenem alone was considered as MBL Positive. Similarly, for detecting carbapenemase Modified Carbapenem Inactivation Method (mCIM) was used. Results: P. aeruginosa was found to be the predominant organism (13.99%). Among 20 P. aeruginosa isolates resistant to imipenem and meropenem, 20% were found to be carbapenemase producer by mCIM assay and 15% were found to be MBL producers by Imipenem-Combined disk method. High percentage of MBL producing isolates of P. aeruginosa were found resistant towards tested antibiotics. Conclusion: This study reports that the clinical isolates of Pseudomonas aeruginosa have the ability to produce MBL. The increasing and rapid spread of P. aeruginosa, as well as the rate of drug resistance among the isolates, was found to be a worrisome situation.